GM-021 Changes caused by implementation of the ABC (Activity Based Costing) method for drug supply in a French university hospital. (24th February 2014) - Zecchini, C; Brudieu, E; Barny, M; Planes, S; Gibert, P; Trivin, C; Foroni, L; Allenet, B
Abstract : Background: Drug supply and stock management are part of the hospital pharmacist's job. Financial restraints imposed by our institution have led us to consider reducing the value of drugs stocked within the pharmacy. Therefore we decided to implement the ABC (Activity Based Costing) method for drug supply. Purpose: To present results obtained by this method in our pharmacy. Materials and methods: About 1800 drugs were divided into three classes: class A represents 20% in quantity and 80% of the stock value, class B represents 30% in quantity and 15% of the stock value and class C represents 50% in quantity and 5% of the stock value. If possible, class A drugs were ordered twice a month; class B drugs once a month, and class C every 45 days. Simultaneously indicators were used to follow up the procedure. This method was used from June to August. Results: A 7.8% drop in the average stock value was recorded after two months; it fell from 3.2 million euros to 2.9 million euros (maximum 3.5 million euros, minimum 2.6 million over the 3 months study). Stock coverage decreased from 17.4 days in June to 11.7 in August for expensive drugs and from 46.9 days to 32.0 for other drugs. At the same time, the number of order lines to manufacturers rose from 1, 943 lines in June to 2, 003 in July and to 1, 896 in August. Conclusions: This method cannot be used for all drugs, such as antidotes, which require buffer stock. This management approach has helped us to reduce stock value consistently. We will also have to include the acquisition cost in the global approach to the drug supply chain. No conflict of interest.